Analisis Pemecahan Masalah dalam Menyelesaikan Soal Kubus dan Balok untuk Siswa Kelas VIII SMP Negeri 4 Loli - Dangu, Ivan Aris Nono; Lede, Yulius Keremata; Making, Samuel Rex M; Kaleka, Yohanes Umbu (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The research is a type of quantitative descriptive research that which to analyze student problem solving through test score data give cube and block material at SMP Negeri 4 Loli. Students sampling was carried out by a teacher consitsting of two students. This study uses indicators and guidelines according to polya. The data collection technique used was by giving test questions to students for analysis.the result of the analysis in this study were that students wereonly able to complete 2 indicators and ignored the other 2 indicators, where students did not apply indicators 2 and 4 in all questions, while for indicators 1 and 3 students did so but there were still errors